Macro-Econometric Modeling of Social Insecurity, Foreign Direct Investments and Economic Growth Association - Ikpe, Marius; Nteegah, Alwell (International Journal of Social Sciences and Management, 2014)
Social insecurity has in recent time constituted a major hurdle to the Nigeria authorities. Theoretically, it is believed to have a strong negative link with Foreign Direct Investment (FDI) and levels of economic growth. This in Nigeria’s context ranges from Niger Delta crises, to the un-going Boko-Haram Islamists Militants insurgency. Given paucity of empirical literature on this line of investigation into this form of socioeconomic problem, this study empirically examines the link amongst social insecurity, FDI and growth of the Nigerian economy. The study adopted the Augmented Cob-Douglas production function in its analysis, introducing the variable (social insecurity) into the FDI model and subsequently traces its impact on economic growth. Result indicates that social insecurity stimulates the inflow of foreign technology, rather than inhibit it. The paper attributes this to merging of these distinct forms of social insecurity in the study and consequently recommend an explicit examination of these forms of social insecurity-FDI association Nigeria. DOI: http://dx.doi.org/10.3126/ijssm.v1i4.10944 Int. J. Soc. Sci. Manage. Vol-1, issue-4: 129-138